1970
DOI: 10.1136/bmj.4.5732.404
|View full text |Cite
|
Sign up to set email alerts
|

Fallacy of the Fundal Height

Abstract: Summary: The method of estimating gestational age from the height of the fundus uteri during pregnancy has been investigated. Such wide variations occur in the length of the maternal abdomen and umbilical position and in the level of the uterine fundus at each gestational age that the method is not reliable. Assessment of uterine size by pelvic examination in the first trimester of pregnancy correlates more closely with gestational age than assessments made by abdominal palpation of the uterus at a later time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(44 citation statements)
references
References 0 publications
2
42
0
Order By: Relevance
“…Robinson noted that uterine size determination by bimanual examination produced incorrect assessments by more than two weeks in over 30% of patients [6]. Similarly, fundal height estimation does not provide a reliable guide to predicting gestational age with up to eight weeks variation in gestational age for any particular fundal height measurement during the second and third trimesters [7]. In addition, quickening or initial perception of fetal movement can vary greatly among women.…”
Section: Clinical Methods For Determining Gestational Agementioning
confidence: 97%
“…Robinson noted that uterine size determination by bimanual examination produced incorrect assessments by more than two weeks in over 30% of patients [6]. Similarly, fundal height estimation does not provide a reliable guide to predicting gestational age with up to eight weeks variation in gestational age for any particular fundal height measurement during the second and third trimesters [7]. In addition, quickening or initial perception of fetal movement can vary greatly among women.…”
Section: Clinical Methods For Determining Gestational Agementioning
confidence: 97%
“…In addition, traditional methods for appreciating fetal development (inspection and fundal height measurement) are unreliable [18,19]. It is therefore necessary to use reliable formulas for echographic fetal weight estimation, as weight in association with gestational age and markers of fetal well-being, may play an important role in the obstetrical management.…”
Section: Discussionmentioning
confidence: 99%
“…Beazley and Underhill reported wide patient variation of their measurements and questioned the clinical relevance of this parameter 8 . Belizan et al and Calvert et al, on the contrary, found the procedure to be simple inexpensive and reliable method of determining fetal age, and a useful screening test for intrauterine growth restriction 9,10 .…”
mentioning
confidence: 99%